(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Precise Point Positioning (PPP) is an aspect of Global Navigational Satellite System (GNSS) technique that uses one satellite receiver to determine position, velocity and time of points on the earth’s surface. PPP could be used globally for a wide range of applications such as positioning in remote areas and positioning where there are lacks of control networks. In order words, PPP is deployed wherever reference stations are not available for it does not transfer local error about. The aim of this study is to verify the consistency of precise point positioning data in cadastral surveying. Selected points were observed 5 times within the period of 12 months. Each observation lasted 60 minutes for each station. The raw GNSS data were downloaded from the receiver into a computer, and converted to RINEX file which were later uploaded to online post-processing service. The results were subjected to standard deviation and confidence interval computations. The results were in centimeter levels. Therefore, the PPP is recommended for use in static mode for control establishments in areas where there are no controls for surveying and mapping.